SIP mediated services - Reid, G.; Aparicio, F. J.; Low, A. L. Y. (SPRINGER, 2007)
In this paper we discuss how we can use the session initiation protocol (SIP) to offer advanced services for mobile users over BT's 21st Century Network (21CN). We provide a brief overview of the advantages of using SIP and describe how SIP can play a vital role in today's and future heterogeneous networks, such as BT's 21CN. We demonstrate some advantages of using SIP for handover in these varied networks and we compare it against using other methods for handover, e. g. mobile IP.